(untitled) (LACCEI, 2024)
Currently, retail is being influenced by digital platforms, leading companies even at a global level to scale in each of their commercial activities. The objective of this research is to identify which social media strategies are appropriate for a baby clothing retail company. The methodology used in this research is descriptive with a mixed approach in order to collect information through qualitative and quantitative methods. For which a survey with 10 questions on a Likert scale was conducted through Google Forms to customers. An interview was also carried out to learn about the strategies applied by the company, with 9 open-ended questions. From the quantitative point of view, there is a 48% of acceptance of the contents disclosed in the digital platforms and 46.6% of respondents find it pleasant to recommend the brand to acquaintances or relatives. From the quantitative point of view, an assertive communication is identified, giving answers to concerns such as presenting products on digital platforms without neglecting the level of attention both internally and externally as a strategy of conviction and continuous improvement, all this supported by the community manager. It is concluded that the company has an excellent synergy with its customers influenced by its content in the networks and adequate attention in online sales.